PTH-069 Active Tuberculosis in Patients with Inflammatory Bowel Disease After Treatment with Anti-TNF Therapy. (17th August 2016) - Owen, L; Thi, AA; Bouri, S; Wolfson, P; Abbara, A; John, L; Davidson, RN; Hart, AL
Abstract : Introduction: Anti-tumour necrosis factor agents (anti–TNF) are major advances in the management of inflammatory bowel disease (IBD) however they are associated with a 5 fold increased risk of Mycobacterium tuberculosis (TB) infection. All patients should be screened for latent TB infection (LTBI) prior to anti-TNF therapy. Here, we review active TB cases after anti-TNF therapy to identify lessons to be learned. Methods: All patients with IBD treated with anti-TNF between March 2007-November 2015 were identified from pharmacy database. Those who developed active TB were identified from the London TB register. Clinical and electronic notes were reviewed. LTBI screening is with history, Chest X-Ray (CXR) and tuberculin skin test (TST) before July 2013 or Quantiferon Gold Assay (QFT-G) after July 2013. Results: Of 596 patients treated with anti-TNF, 6 had active TB. 5 had Crohn's and 1 had Ulcerative Colitis. 3 were male, none had HIV. Age range was 24–49 years. 5 were Caucasian, 1 was UK born but of Pakistani origin. 3 were on Adalimumab (ADA) at time of TB diagnosis and 2 on Infliximab (IFX), 3 were on at least 1 other immunosuppressive. 1 was not on anti-TNFs at TB diagnosis but received IFX 3 months earlier. Time from initiation of anti-TNF to TB diagnosis ranged from 3–41 months (median:13, IQR = 32). 3 had culture confirmed TB, 1 was MTB complex PCR positive but culture negative and 2 had presumed TB. All isolated cultures were fully sensitive. 2 had miliary TB, 2 abdominal TB, 1 pleuro-pulmonary TB and 1 both pulmonary and pericardial TB. Treatment duration was 6–12 months, 5 patients completed treatment and 1 remains on treatment. 3 had prior vaccination for TB, 1 did not and the vaccination status of 2 was unknown. 4 patients had negative TSTs pre-anti-TNF (3 while immunosuppressed), 1 had an indeterminate QFT-G test (while immunosuppressed) and 1 had neither. All patients had normal CXR prior to anti-TNF. No patients received LTBI treatment. Conclusion: All cases were considered low epidemiological risk for LTBI . None had a positive TST or QFT-G, however the risk of false negatives is high in immunosuppression. As some patients screened may receive prolonged and recurrent courses of anti-TNF, we recommend discussion around when patients should be rescreened. It is unclear if these cases represent de novo infection or reactivation of latent disease but re-screening may have identified them at the latent stage. As it is not possible to prevent all cases of active TB, there must be continued focus on prompt diagnosis and treatment, alongside comprehensive screening by working with local TB services. Disclosure of Interest: None Declared